2005
DOI: 10.1038/sj.npp.1300859
|View full text |Cite
|
Sign up to set email alerts
|

Do Preclinical Findings of Methamphetamine-Induced Motor Abnormalities Translate to an Observable Clinical Phenotype?

Abstract: This review summarizes the preclinical literature of the effects of methamphetamine (MA) on subcortical dopaminergic and GABAergic mechanisms underlying motor behavior with the goal of elucidating the clinical presentation of human MA-induced movement disorders. Acute and chronic MA exposure in laboratory animal can lead to a variety of motor dysfunctions including increased locomotor activity, stereotypies, diminished or enhanced response times, and parkinsonian-like features. With the exception of psychomoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 104 publications
2
40
0
Order By: Relevance
“…Miller et al showed that toxic doses of MA increase the expression of GFAP in the striatum of the C57BL/6J mice [49]. Similar effects were seen in other brain regions including cerebellum and hippocampus [14,50]. Prolonged MA exposure causes neurotoxicity by apoptotic and neurotoxic mechanisms in striatal cells [10,51].…”
Section: Neurotoxicity Of Methamphetaminementioning
confidence: 61%
See 2 more Smart Citations
“…Miller et al showed that toxic doses of MA increase the expression of GFAP in the striatum of the C57BL/6J mice [49]. Similar effects were seen in other brain regions including cerebellum and hippocampus [14,50]. Prolonged MA exposure causes neurotoxicity by apoptotic and neurotoxic mechanisms in striatal cells [10,51].…”
Section: Neurotoxicity Of Methamphetaminementioning
confidence: 61%
“…Studies have shown that alpha-methyl-tyrosine (AMT) attenuates, whereas reserpine potentiates the releasing action of AMP [27,28]. Acute and prolonged MA exposure can elevate postsynaptic nigrostriatal DA [14,22]. Acute MA administration can result in increased dopamine turnover in the caudate nucleus, and changes in monoamines and peptides in the basal ganglia [14,29,30].…”
Section: Neurochemical and Pharmacological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson's disease psychomotor disturbances have been reported among methamphetamine heavy users [61]. To confirm this hypothesis, a retrospective case-controlled study revealed that prolonged use of methamphetamine is associated with an eight-fold increased risk of Parkinson's disease with an average of 27 years between amphetamine exposure and the onset of signs [62].…”
Section: Parkinson's Diseasementioning
confidence: 87%
“…Methamphetamine abuse has been implicated in the onset of hyperkinetic disorders including chorea. 8 One could further speculate on whether our patient developed tardive dyskinesia on the basis of exposure to fluoxetine.…”
Section: Discussionmentioning
confidence: 99%